Contrasting bean analysis system based on YOLOv5 and a neural network model using the interval type-2 fuzzy set approach - Rodriguez Alvarez, José Luis; García-Alcaraz, Jorge Luis; Puig i Vidal, Rita; Soto Cabral, Alondra (2024)
https://link.springer.com/article/10.1007/s00521-024-10217-y